Efek Mediasi Keterlibatan Kerja dan Komitmen Organisasi pada Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai Regional II PT. Perkebunan Nusantara IV - Rosnida Br Sinaga; Susi Handayani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Employee performance is one of the most important things in an institution because it plays a role in improving the quality of human resources. There are several factors that can influence performance, including organizational culture, work involvement and organizational commitment. The purpose of this research is to examine the role of work involvement and organizational commitment in mediating organizational culture and employee performance. The population in this study were all employees of regional II PT. Perkebunan Nusantara IV. The sampling technique in this research used the Slovin formula and a sample of 80 respondents was obtained. The data collection technique uses a questionnaire with a Likert scale. The data analysis method used is Partial Least Square (PLS) using SmartPLS 3.0 Software. The results of this research indicate that organizational culture influences employee performance. Organizational culture influences work engagement. Organizational culture influences organizational commitment. Work involvement influences employee performance. Organizational commitment influences employee performance. Work engagement is able to mediate the influence of organizational culture on employee performance. Organizational commitment is able to mediate the influence of organizational culture on employee performance.